"I would prefer to have my health care provided over a cup of tea any day": recommendations by urban Métis women to improve access to health and social services in Toronto for the Métis community. (September 2019) - Monchalin, Renée; Smylie, Janet; Bourgeois, Cheryllee; Firestone, Michelle
This article reports on recommendations made by urban Métis women for improving access to health and social services in Toronto, Canada. By applying a conversational method, this research followed up with a subgroup of urban Métis women who participated in the Our Health Counts Toronto longitudinal cohort. Métis women ( n = 11) provided holistic and practical recommendations for improving access to health and social services. These recommendations include (a) Métis presence, (b) holistic interior design, (c) Métis specific or informed service space, (d) welcoming reception/front desk, and (e) culturally informed service providers. During the conversations, the women shared positive experiences with an Indigenous-informed midwifery practice called Seventh Generation Midwives Toronto. Examples from the women will be provided of Seventh Generation Midwives Toronto to illustrate how the recommendations may look in practice. This research illustrates that Métis women hold solutions for improving access to health and social services for the Métis community.